Stoic Romanticism and the Ethics of Emotion - Risinger, Jacob (Princeton University Press, 2021)
Cover -- Contents -- Acknowledgments -- List of Abbreviations -- Introduction -- Chapter 1. Stoic Moral Sentimentalism from Shaftesbury to Wollstonecraft -- Chapter 2. Wordsworth and Godwin in "Frozen Regions" -- Chapter 3. Coleridge, Lyric Askesis, and Living Form -- Chapter 4. The True Social Art: Byron and the Character of Stoicism -- Chapter 5. Stoic Futurity in Sarah Scott and Mary Shelley -- Chapter 6. Emerson, Stoic Cosmopolitanism, and the Conduct of Life -- Notes -- Bibliography -- Index.